Analysis of Components of The Scientific Approach in The X-Grade Students of Physics For SMA - Hastil Hanifah; - Akmam; - Gusnedi; Wahyuni Satria Dewi (Universitas Negeri Padang, 2021)
Teachers as educators must be selective in choosing the right physics textbooks in order to help students achieve the expected competencies. However, textbooks that are suitable for use in accordance with the demands off the 2013 Curriculum, especially in Padang Pariaman Regency, have not been carried out. Therefore, a research was conducted which aims was determine the application of the components of the scientific approach in the second class X Semester 2 SMA Physics textbook used in SMA throughout the Padang Pariman Regency. This research is a descriptive studyswith a qualitative approach. The population in this study was the 2013 class X high school physics textbook used by 20 public high schools in Padang Pariaman Regency. Textbook sampling for analysis using saturated sampling technique. The data in this study were taken using an analytical instrument of the application of the scientific approach component developed from Permendikbud Number 103 of 2014. The results showed that the application off the scientific approach component of the textbooks analyzed was categorized quite appropriate, meaning that overall the five textbooks analyzed had not facilitated each component of the scientific approach optimally. Textbooks with the highest percentage of the fulfillment of the Scientific approach components are found in textbooks with the code Book A with an average percentage of 45.8%, and the lowest percentage is in Book C with an average percentage of 32.3%.